The Effects of Whole-Body Vibration Exercise Combined With an Isocaloric High-Fructose Diet on Osteoporosis and Immunomodulation in Ovariectomized Mice - Tsai, Syun-Hui; Tseng, Yu-Hwei; Chiou, Wen-Fei; Chen, Shih-Ming; Chung, Yi; Wei, Wen-Chi; Huang, Wen-Ching (Frontiers in Nutrition, 2022)
Background:Osteoporosis and immune-associated disorders are highly prevalent among menopausal women, and diet control and exercise exert beneficial effects on physiological modulation in this population. A controlled diet with a low-fat content and a balanced caloric intake improves menopausal health, but the health effects of excessive fructose consumption on menopausal women are yet to be confirmed. In addition, whole-body vibration (WBV), a safe passive-training method, has been shown to have multiple beneficial effects on metabolism regulation, obesity, and bone health. Methods: The ovariectomized (OVX) C57BL/6J model was used to verify the effects of WBV combined with a high-fructose diet (HFrD) for 16 weeks on physiological modulation and immune responses. The mice were randomly allocated to sham, OVX, OVX+HFrD, and OVX+HFrD+WBV groups, which were administered with the indicated ovariectomy, dietary and WBV training treatments. We conducted growth, dietary intake, glucose homeostasis, body composition, immunity, inflammation, histopathology, and osteoporotic assessments (primary outcomes). Results:Our results showed that the isocaloric HFrD in OVX mice negated estrogen-deficiency-associated obesity, but that risk factors such as total cholesterol, glucose intolerance, osteoporosis, and liver steatosis still contributed to the development of metabolic diseases. Immune homeostasis in the OVX mice was also negatively affected by the HFrD diet, via the comprehensive stimulation of T cell activation, causing inflammation. The WBV intervention combined with the HFrD model significantly ameliorated weight gain, glucose intolerance, total cholesterol, and inflammatory cytokines (interferon gamma [IFN-γ], interleukin [IL]-17, and IL-4) in the OVX mice, although osteoporosis and liver steatosis were not affected compared to the negative control group. These findings indicate that an isocaloric high-fructose diet alone may not result in menopausal obesity, but that some deleterious physiological impacts still exist. Conclusion:The WBV method may modulate the physiological impacts of menopause and the HFrD diet, and should be considered as an alternative exercise prescription for people with poor compliance or who are unable or unwilling to use traditional methods to improve their health. In future studies, using the WBV method as a preventive or therapeutic strategy, combined with nutritional interventions, medication, and other exercise prescriptions, may prove beneficial for maintaining health in menopausal women.